Thinking with the book and about the book - Dmytruk, Y. (AgroChemistry and Soil Science, 2021)
You see a review of a modern scientific publication - the book by Boris Boinchan and David Dent «Farming the Black Earth. Adaptive Soil Management». Prut Publishing House, Chisinau, 2020. The book is published in Russian and is a translation from the English edition «Farming the Black Earth», by Boris Boincean, David Dent. Springer, 2019 (https://www.springer.com/gp/book/9783030225322 ).The author of the article does not call his work a review, but makes a postscript - "instead of a review." And this is really not only a characteristic of a new scientific publication by famous foreign authors about the soil, published in one of the most famous European edition and its translation, but is a response of author himself, his thoughts on the state and status of soil in the world and the problems so clearly outlined in recommended book. The main goal of both book and review is to draw public attention to soil problems and push society to their soil solution, with the understanding that no phenomenon of nature and society can’t occur if it is not prepared by the previous development of other things.